A brief overview on finite element analysis for mechanics of proton exchange membrane fuel cell / Abdul Muhaimin Abdul Aziz ... [et al.] - Abdul Aziz, Abdul Muhaimin; Ng, Wei Shi; Mohamad Yunus, Rozan; Mohd Anuar, Mohd Afzan (Universiti Teknologi MARA, 2024)
Hydrogen energy is an ideal alternative for energy-intensive industrial processes, long-distance transportation, and enabling the integration of decentralized renewable energy sources like solar and wind power. Many countries have implemented strategies for the development of hydrogen energy. Proton exchange membrane fuel cells (PEMFC) are a highly efficient hydrogen conversion technology that can be utilised in a variety of applications, including backup power systems, portable electronics, and transportation, due to its high-power density and simple architecture. Finite element analysis (FEA) is a prominent numerical tool to simulate and to predict the mechanical behaviour of PEMFC under operating conditions. The main goal of this paper is to conduct a review on the utilisation of FEA in improving the performance of PEMFC. The FEA utilisation to evaluate the geometrical design of PEMFC end plate is first discussed, followed by fatigue life of PEMFC stack. Finally, the design optimisation of PEMFC performed in various investigations is also reported. Well validated FEA is found to be a powerful tool to evaluate the mechanics of PEMFC. It can be integrated with modern optimisation methods to improve the performance of PEMFC.